Educator Paradigms in Deep Learning in Relation to Islamic Educational Traditions - Nanang Budianto (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study is grounded in a fundamental problem in contemporary educational practices, which remain dominated by surface learning, thereby failing to foster deep understanding, reflective awareness, and the integration of values in learners. In the context of Islamic education, this issue becomes more complex due to the dichotomy between cognitive and spiritual dimensions. Therefore, this study aims to analyze and reconstruct the paradigm of educators in deep learning by integrating the roles of mu‘allim, murabbi, and mu’addib, as well as to identify relevant pedagogical principles. This research employs a qualitative approach through library research, utilizing content analysis of both modern educational theories and Islamic educational literature. The findings reveal that the educator paradigm must be integrative, positioning teachers as transformative agents who connect cognitive, affective, and spiritual dimensions. Furthermore, five key pedagogical principles are identified: meaningful, reflective, contextual, value-based, and holistic learning. The implications of this study highlight the importance of developing learning models that are not only academically effective but also capable of shaping learners’ character, awareness, and moral responsibility in a sustainable manner.